2015
DOI: 10.1016/j.virusres.2014.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Host–pathogen interactions during porcine reproductive and respiratory syndrome virus 1 infection of piglets

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is a major disease affecting pigs worldwide and resulting in considerable economic losses. While PRRS is a global phenomenon, the causative viruses PRRSV-1 (first detected in Europe) and PRRSV-2 (isolated in North America) are genetically and biologically distinct. In addition, the disease outcome is directly linked to co-infections associated with the porcine respiratory disease complex and the host response is variable between different breeds of pigs. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…It has been shown that, in terms of virulence, antigenic characteristics and immunological responses following experimental infection, the Belarusian Lena subtype 3 strain differed from subtype 1 strains from Western Europe being generally more pathogenic for pigs (Karniychuk et al, 2010;Weesendorp et al, 2013aWeesendorp et al, , 2014. Later, another subtype 3 Belarusian strain SU1-bel, which was characterized in vitro and in in vivo challenge experiments also proved to be significantly more virulent than Western European strains (Morgan et al, 2014(Morgan et al, , 2013Salguero et al, 2015). At present, no data are available about the biological characteristics of East European PRRSV-1 strains from other genetic subtypes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, in terms of virulence, antigenic characteristics and immunological responses following experimental infection, the Belarusian Lena subtype 3 strain differed from subtype 1 strains from Western Europe being generally more pathogenic for pigs (Karniychuk et al, 2010;Weesendorp et al, 2013aWeesendorp et al, , 2014. Later, another subtype 3 Belarusian strain SU1-bel, which was characterized in vitro and in in vivo challenge experiments also proved to be significantly more virulent than Western European strains (Morgan et al, 2014(Morgan et al, , 2013Salguero et al, 2015). At present, no data are available about the biological characteristics of East European PRRSV-1 strains from other genetic subtypes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest the presence of alternatively activated M2 macrophages and reflect the requirement for enhanced phagocytosis after the increased cell death (tissue remodelling). The reduced generation of T cells could result in an impaired T cell response, as previously suggested (Rodríguez-Gómez et al, 2013;Salguero et al, 2015).…”
Section: Discussionmentioning
confidence: 72%
“…More recently, HP-PRRSV strains were also identified in Eastern Europe (Karniychuk et al, 2010). The emergence of HP-PRRSV in Asia and Eastern Europe have revived the interest in understanding the immunobiology of PRRSV strains of differing virulence Salguero et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, development of new PRRSV vaccines faces many challenges because of the high variability and the diverse mechanisms that the virus employs to evade the immune Uribe-Campero et al 1601 response (Huang et al, 2015;Salguero et al, 2015). A number of strategies including recombinant production of different PRRSV antigens in various systems have been tested (Qiu et al, 2005;Jiang et al, 2006;Zheng et al, 2007;Li et al, 2009a, b;Cruz et al, 2010;Chen and Liu, 2011;Chia et al, 2011;Vimolmangkang et al, 2012;Chan et al, 2013;Nam et al, 2013).…”
Section: Introductionmentioning
confidence: 99%